Studi Kandungan Logam Berat Kadmium (Cd) pada Spesies Ikan Kembung (Rastrelliger kanagurta) dan Kerang Darah (Anadara granosa) di Perairan Manyar, Gresik dan di Perairan Jabon, Sidoarjo [The Study Of Heavy Metal Content Cadmium (Cd) Species On (Rastrelliger kanagurata) And (Anadara granosa) In Manyar, Gresik And Jabon Sidoarjo] - Boedi Setya Rahardja; Muhammad Nur Faith Zulkarnain; Moch. Amin Alamsjah (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Marine pollution to be contamination that often occurs at this time. Commonly, one of pollutants found at sea is heavy metal pollution because heavy metal can be dangerous, it is not degraded by the body, toxicity properties in living organisms even at low concentrations and can be accumulated in a certain period. Heavy metals are found in marine waters are polluted Cadmium (Cd). Biota were used as indicators of environmental pollution marine white is fish and shellfish bloating blood. Standard National Indonesia (SNI) based, maximum Content of Cadmium in the body of organisms was 0,2 mg/kg. The aimed of the study to determine differences in Heavy Metal Cadmium fish and shellfish bloating blood contained in Manyar, Gresik waters and the Jabon, Sidoarjo waters. This research is descriptive and the data obtained and analyzed Independent Samples T 2 test. Cadmium content analysis done by destructive methods then performed using Atomic Absorbance readings Spectrophotometric (AAS). Based on analysis of the has been done that cadmium content the heavy metal of cadmium content in the Manyar Gresik water, in Gresik on Mackerel average rate (0.12888) ppm, and still below the Indonesian National Standard threshold (SNI 0,2 mg/kg), and blood clams at (1.24483) ppm have exceeded the Indonesian National Standard (SNI 0,2 mg/kg). The content of cadmium in the Jabon Sidoarjo waters, the mackerel average rate (0,01891) ppm, and still below the threshold Indonesian National Standard (SNI 0,2 mg/kg), and blood clams at (0,69937) ppm, has exceeded threshold of the Indonesian National Standard (SNI 0,2 mg/kg).